A Taxonomic Revision of Arapatiella (Fabaceae: Caesalpinioideae): An Endemic and Threatened Genus from the Brazilian Coast - Rodrigues, Ana Tereza Novaes Parga; Falcão, Marcus José De Azevedo; Mansano, Vidal De Freitas (Phytotaxa, 2023)
Arapatiella is a genus of Fabaceae (Leguminosae) of the subfamily Caesalpinioideae, endemic to the Atlantic Forest on the coast of the Brazilian state of Bahia. Popularly known in its region of occurrence due to the commercial use of its wood, Arapatiella is subject to strong influence of anthropic action. Currently, two species of trees are described for the genus: Arapatiella psilophylla and Arapatiella emarginata. However, the circumscription of these taxa is based on old works made with reduced sets of specimens, in need to be stronger delimited. Given this, we conducted a taxonomic and nomenclatural review of the genus based on an integrative species concept. We examined 125 gatherings from 26 national and international herbaria and living individuals collected during in situ expeditions. From the herbarium and field analyses, it was possible to state that the previous taxa circumscriptions do not fully correspond to the currently available specimen set and aren’t strong enough to delimit two species. Therefore, we chose to recombine the species as two varieties: Arapatiella psilophylla var. psilophylla and Arapatiella psilophylla var. emarginata, separated mainly by leaflet apex, stipule size, pubescence, and size of inflorescences and flowers. Distribution maps, taxonomic comments, an identification key, and a nomenclatural revision, including two new lectotypifications, are presented.